Capital exports to rising Eastern Europe: Would voters go for it? - Günther G. Schulze (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
The paper addresses the question whether voters would favor a restriction on capital exports to the East, and if so, to what extent. In a two country framework, it is shown that an unrestricted capital outflow is not optimal, in the traditional sense of a social welfare maximizing benevolent dictator. Furthermore, capital export may lead to unemployment and a loss of output in the exporting country if a minimum wage constraint comes into effect. Nevertheless, it may still be optimal to encounter a certain loss in employment and production because of a positive factor terms of trade effect. The preferences of individuals who are differently endowed with 'capital and labor depend on their endowment ratio: E.g., an individual whose capital-labor endowment ratio exceeds the figure for the economy will prefer less-than-optimal curbing of capital outflow. If the policy concerning capital exports is decided upon via majority voting, it is the median voter's optimal policy that is finally adopted. This implies that the restriction on capital exports would presumably be tighter than in the traditional understanding of a benevolent dictator.
Keywords: 330; Kapitalexport; Ökonomische Theorie der Demokratie; Theorie; Westliche Staaten; Osteuropa